Acute transverse myelitis revealing ankylosing spondylitis: A case report and literature review. Issue 10 (4th October 2021) - Boussaid, Soumaya; Rahmouni, Safa; Rekik, Sonia; Jammali, Samia; Cheour, Elhem; Sahli, Hela; Elleuch, Mohamed
Abstract: When faced with a patient with acute myelopathy, thorough investigations should be undertaken to determine the cause. Ankylosing spondylitis should be kept in mind as a possible cause. Abstract : (A) MRI of the spine (T2‐weighted) sagittal section showing long‐segment hyperintensity involving the spinal cord extending from T6 to T11 level (black arrow) and high T2 signal of supero‐anterior corners of vertebrae from T7 to T9 corresponding to Romanus lesions (white arrows). (B) MRI of the pelvis (T1‐weighted) edema and erosions of the sacroiliac joints. (C) MRI of the pelvis (T1Fatsat‐weighted with gadolinium) edema and erosions of the sacroiliac joints.